2007
DOI: 10.1007/s00436-006-0435-1
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity in the trypanorhynch cestode Tentacularia coryphaenae Bosc, 1797: evidence for a cosmopolitan distribution and low host specificity in the teleost intermediate host

Abstract: Partial large subunit (28S) rRNA gene (LSU) sequences were studied from Tentacularia coryphaenae (Cestoda: Trypanorhyncha) plerocercoids from the southern Java coast, Indonesia, collected from two different localities and five different host species. The teleost hosts belonged to four fish families with an overlapping depth range of 0-885 m. The LSU sequences were identical, demonstrating that all specimens belonged to the same species. They also corresponded to a sequence of T. coryphaenae from the Blue shark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 14 publications
5
27
0
Order By: Relevance
“…Kellermanns et al (2007) suggested that a constant gene flow in different anisakid nematodes is caused by a) extensive final host migration in the case of A. simplex (s.s.), b) an overlapping distribution of final host populations along the continental shelves for Pseudoterranova decipiens (s.s.), and c) a low host specificity and large population size in the intermediate and final hosts for Hysterothylacium aduncum. Palm et al (2007) suggested d) extensive final as well as intermediate host migration as being responsible for a high gene flow in a cosmopolitan fish cestode, the trypanorhynch Tentacularia coryphaenae. A. typica, as a tropical anisakid, seems to follow the latter dispersal mechanism, being more similar to the trypanorhynch than to the congener A. simplex (s.s.), as can be seen in highly overlapping fish intermediate hosts in the tropics (Table 4 vs .…”
Section: Phycis Phycis As Intermediate Hosts)mentioning
confidence: 99%
“…Kellermanns et al (2007) suggested that a constant gene flow in different anisakid nematodes is caused by a) extensive final host migration in the case of A. simplex (s.s.), b) an overlapping distribution of final host populations along the continental shelves for Pseudoterranova decipiens (s.s.), and c) a low host specificity and large population size in the intermediate and final hosts for Hysterothylacium aduncum. Palm et al (2007) suggested d) extensive final as well as intermediate host migration as being responsible for a high gene flow in a cosmopolitan fish cestode, the trypanorhynch Tentacularia coryphaenae. A. typica, as a tropical anisakid, seems to follow the latter dispersal mechanism, being more similar to the trypanorhynch than to the congener A. simplex (s.s.), as can be seen in highly overlapping fish intermediate hosts in the tropics (Table 4 vs .…”
Section: Phycis Phycis As Intermediate Hosts)mentioning
confidence: 99%
“…Various aspects of Trypanorhyncha cestodes have been studied by some scientific researchers such as their morphological, taxonomic, and genetic diversity (Casado et al 1999;Justine et al 2012;Marques et al 2005;Palm 2008;Palm et al , 2007. The present study aims the identification of Trypanorhyncha cestodes parasitizing P. patagonicus and X. rasile, and their parasitological indices and sites of infection.…”
Section: Introductionmentioning
confidence: 98%
“…Whilst the adults are typically found in the stomach and intestine of sharks and rays, larval forms infect a wide variety of marine invertebrates and teleosts. Larval worms, especially, have low host specificity (Palm and Caira, 2008) and a wide zoogeographical, or even cosmopolitan, distribution (Palm 2004, Palm et al 2007. Being widely distributed from brackish waters into the deep sea, the highest species diversity of trypanorhynchs can be found in coastal tropical waters of the Indo-Australian region (Palm et al 2009).…”
Section: Introductionmentioning
confidence: 99%